Assessing infrastructure interdependencies: the challenge of risk analysis for complex adaptive systems. (24th February 2004) - Brown, Theresa; Beyeler, Walt; Barton, Dianne
Infrastructures are a complex set of interconnected, interdependent, adaptive systems on which the nation, manufacturing systems and individuals depend. Understanding the potential consequences of infrastructure interdependencies, as the infrastructures evolve and the regulations governing their operation change, is at the heart of our infrastructure interdependencies research program. This program includes development of analysis methods and simulation tools for evaluating the potential effects of disruptions and for prioritising risks. Fundamental infrastructures simulated using these tools include; transportation, telecommunications, electric power, banking and finance, water, agriculture, emergency services, fossil fuels, and government. The complexity of the infrastructures and their interactions prevent us from knowing a priori how these interactions will influence individuals, states or the nation; the consequences of policy decisions; vulnerabilities due to interdependencies, natural disasters, malevolent threats and aging; or vulnerabilities that need to be eliminated in order to assure individual, state or national economic security. The goal of the interdependency analyses is to identify significant risks to critical systems, arising from interconnection, and effective mechanisms for mitigating those risks. This article presents the infrastructure interdependency assessment process, modelling tools developed to support that process and examples of assessment results.